(5Z^4-3Z^6)-(2Z^2+7Z^4)-(7Z^6-4Z^2)
Упрости выражение и представь в стандартном виде

1

Ответы и объяснения

2013-12-20T14:25:22+00:00
Выражение: 5*Z^4-3*Z^6-(2*Z^2+7*Z^4)-(7*Z^6-4*Z^2)
Решаем по действиям:
1. 5*Z^4-3*Z^6-(2*Z^2+7*Z^4)=5*Z^4-3*Z^6-2*Z^2-7*Z^4
2. 5*Z^4-7*Z^4=-2*Z^4
3. -2*Z^4-3*Z^6-2*Z^2-(7*Z^6-4*Z^2)=-2*Z^4-3*Z^6-2*Z^2-7*Z^6+4*Z^2
4. -3*Z^6-7*Z^6=-10*Z^6
5. -2*Z^2+4*Z^2=2*Z^2
Решаем по шагам:
1. 5*Z^4-3*Z^6-2*Z^2-7*Z^4-(7*Z^6-4*Z^2)
2. -2*Z^4-3*Z^6-2*Z^2-(7*Z^6-4*Z^2)
3. -2*Z^4-3*Z^6-2*Z^2-7*Z^6+4*Z^2
4. -2*Z^4-10*Z^6-2*Z^2+4*Z^2
5. -2*Z^4-10*Z^6+2*Z^2
Ответ: -2*Z^4-10*Z^6+2*Z^2